(untitled) (Bangladesh Journal of Neuroscience, 2026)
Background: Amyotrophic lateral sclerosis (ALS) is the most common type of motor neuron disease (MND) where both upper motor neuron (UMN) and lower motor neuron (LMN) are affected. It is a neurodegenerative disease which is relentlessly progressive and presently incurable. Motor unit number estimation (MUNE) can be a valuable tool for assessing ALS. MUNE is an electrophysiological technique that estimates the number of functioning motor units in a given muscle or group of muscles. MUNE is an electrophysiological measurement which is simple and can be done in basic electrophysiology setting. It can be used as a diagnostic as well as prognostic marker of ALS so that patient can undergo an early therapeutic trial. Previous study also shows that it can differentiate ALS from other potential mimic disorders. Objective: The objective of this study is to see association of MUNE with ALS. Methods: This cross-sectional comparative study was done in the Department of Neurology, BSMMU, Dhaka, from January 2020 to September 2021. Total 44 subjects, 22 ALS patients and 22 age & sex matched control group (CG), were enrolled after satisfying the selection criteria. According to El Escorial diagnostic criteria ALS patients were sub grouped into definite, probable and possible ALS. Severity was assessed by ALS functional rating scale-revised (ALSFRS-R). Then electrophysiological study was done to measure MUNE both in ALS patients and control group by multipoint incremental stimulation based method. Collected data were analyzed by SPSS (26 version) for windows software to observe association of MUNE with ALS. Results: MUNE was found significantly reduced in ALS patients than control group (MUNEALS -63.3 ±27.5, MUNECG – 158.3±27.3; p<0.001). Possible, probable and definite ALS patients were also differentiated from control group by MUNE (MUNE Definite– 51.7±19.7, MUNE Probable – 55.8±30.5, MUNE Possible– 79.4±24.2 and MUNECG – 158.3±27.3; p<0.001). MUNE was positively correlated (r = +0.765, p<0.001) with severity status (ALSFRS-R) and negatively correlated (r = -0.755, p<0.001) with duration of disease. Receiver operating characteristic (ROC) curve analysis showed that MUNE reliably differentiated ALS patients from control group with a cut-off value 117.75 exhibiting 99.0% sensitivity and 90.9% specificity. Conclusion: There was significant association of MUNE with ALS. MUNE also reliably differentiated ALS from control group with high diagnostic accuracy. MUNE had also significant association with severity status and duration ofALS.